2022
DOI: 10.1186/s13037-021-00314-5
|View full text |Cite
|
Sign up to set email alerts
|

Operating room efficiency in a low resource setting: a pilot study from a large tertiary referral center in Ethiopia

Abstract: Background The operating room (OR) is one of the most expensive areas of a hospital, requiring large capital and recurring investments, and necessitating efficient throughput to reduce costs per patient encounter. On top of increasing costs, inefficient utilization of operating rooms results in prolonged waiting lists, high rate of cancellation, frustration of OR personnel as well as increased anxiety that negatively impacts the health of patients. This problem is magnified in developing countr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…This team training could facilitate access to the operating room and reduce unforeseen events and financial losses due to cancellations. In a study about 933 elective procedures, a high cancellation rate was observed primarily due to a lack of operating room time and inadequate patient preparation, emphasizing the need for improved patient evaluation workflows, sufficient operating room staffing, and punctual start times to enhance operating room efficiency in settings with a high unmet burden of surgical disease [ 100 ]. Team learning, involving 40 operating room staff, identified key themes such as a commitment to learning, the significance of a safe space in debriefing, and the role of leadership in mitigating hierarchies [ 101 ].…”
Section: Discussionmentioning
confidence: 99%
“…This team training could facilitate access to the operating room and reduce unforeseen events and financial losses due to cancellations. In a study about 933 elective procedures, a high cancellation rate was observed primarily due to a lack of operating room time and inadequate patient preparation, emphasizing the need for improved patient evaluation workflows, sufficient operating room staffing, and punctual start times to enhance operating room efficiency in settings with a high unmet burden of surgical disease [ 100 ]. Team learning, involving 40 operating room staff, identified key themes such as a commitment to learning, the significance of a safe space in debriefing, and the role of leadership in mitigating hierarchies [ 101 ].…”
Section: Discussionmentioning
confidence: 99%
“… 10 Consequently, their application in clinical context is widespread. 11 Therefore, enhancing the efficiency of the operating room and accelerating turnaround times are essential for maximizing hospital and social benefits. 12 In this study, we aimed to analyze the utilization of three different over-bed methods for the stirrup lithotomy position, adhering to the principles of effective and feasible process development and meticulous control of each step to enhance efficiency.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Samuel et al prospectively studied 933 elective surgeries performed in a tertiary hospital in Ethiopia and found that the elective surgery start time was delayed in 93.40% of cases with a mean start time of 9:41660 minutes. 15 Another study of the performance of 9 ORs in a tertiary teaching hospital in Addis Ababa by Tiruneh et al reported an average delay of 43 minutes from the agreed 8:00 am, and only 2.50% of the operations were started as per the schedule communicated before the surgery. 16 The literature described multiple interrelated factors to explain delays in surgery start time and overall OR productivity.…”
Section: Surgical Incision Start Time Was Associated With Operative P...mentioning
confidence: 99%
“…A study in Tikur Anbessa Specialized Hospital in Ethiopia, where 35.8% of elective surgeries were canceled, reported that the most common reasons for cancellation were inadequate OR time and lack of patient preparation, 8.70% and 7.70%, respectively. 15 Feleke et al argued that surgical cancellations were primarily due to patient-related and administrative factors, 31.32% and 26.5%, respectively. 24 Dhafar et al retrospectively audited a total of 120 ORs in 25 hospitals in Saudi Arabia and reported that among the 7.60% (1,238 of 16,211) surgeries canceled, the major contributing factors were related to the patient (42.81%), facility (20.03%), and incomplete work-up (9.45%).…”
Section: Turnover Time and Cancellation Rate Were Not Associated With...mentioning
confidence: 99%